The Influence of Marketing and Production Factor on Troso Weaving Cloth - Khasan Setiaji; Rifalatul Umi (Economics Development Analysis Journal, 2019)
The business performance is influenced by various factors such as marketing strategy and production factor. Both have important roles to improve business performance. However, the number of Troso weaving cloth decreased gradually from 2013 up to 2016. This study aims at knowing the impact of marketing strategy and production factor to the performance of small and medium enterprises on Troso weaving cloth simultaneously and partially. The population was 180 owners of Troso weaving cloth with the sample of 64. The sample was determined by using proportionate random sampling. Then, the variables for this study consist of independent variables that are marketing strategy (X1) and production (X2) factor; and dependent variable that is business performance (Y). Based on the percentage descriptive analysis. The marketing strategy variable has influence as many as 73% with good category, while the production factor influences business performance, 61% with the moderate category. This study has found that marketing strategy and production factor have positive and significant impact partially and simultaneously to the business performance of small and medium enterprises on Troso weaving cloth.